Object-Oriented Modeling and Terminologies for Drug Contraindications - Liu, J. H.; Milstein, C.; Séné, B.; Venot, A. (Methods of Information in Medicine, 1998)
There is no available standardized representation of contraindications that can be used in drug knowledge bases. In this paper, an objectoriented representation of contraindications is proposed that would allow computerized checking of drug prescription safety. It distinguishes four types of contraindications: pathological state, physiological state, findings of investigation procedures, and diagnostic or therapeutic procedures. The vocabulary usable for expressing the contraindications appropriate for automated prescription checking was also investigated. ICDlO (International Classification of Diseases, tenth revision), SNOMED III (Systematized Nomenclature of Medicine), ICPC (International Classification of Primary Care), and ATC (Anatomic Therapeutic and Chemical Classification) were studied as potential sources of standardized vocabulary. A system to support entering data on contraindications into a drug knowledge base, compatible with the proposed structure and using the identified vocabulary sources, is also presented.
Keywords: Drug Contraindications; Drug Prescription; Knowledge Base; Information Modeling